Novel Clinician-Lead Intervention to Address Fear of Cancer Recurrence in Breast Cancer Survivors. Issue 6 (June 2021) - Liu, Jia; Butow, Phyllis; Bui, Kim T.; Serafimovska, Anastasia; Costa, Daniel S. J.; Kiely, Belinda E.; Hui, Mun N.; Goodwin, Annabel; McNeil, Catriona M.; Beith, Jane M.
Abstract : PURPOSE: Fear of cancer recurrence (FCR) affects 50%-70% of cancer survivors. This multicenter, single-arm study sought to determine the participant-rated usefulness of an oncologist-delivered FCR intervention. METHODS: Women who completed treatment for early breast cancer (could be receiving endocrine therapy) with baseline FCR > 0 were invited to participate. FCR was measured using a validated 42-item FCR Inventory. The brief oncologist-delivered intervention entailed (1) FCR normalization; (2) provision of personalized prognostic information; (3) recurrence symptoms education, (4) advice on managing worry, and (5) referral to psycho-oncologist if FCR was high. FCR, depression, and anxiety were assessed preintervention (T0), at 1 week (T1), and 3 months (T2) postintervention. The primary outcome was participant-rated usefulness. Secondary outcomes included feasibility and efficacy. RESULTS: Five oncologists delivered the intervention to 61/255 women invited. Mean age was 58 ± 12 years. Mean time since breast cancer diagnosis was 2.5 ± 1.3 years. Forty-three women (71%) were on adjuvant endocrine therapy. Of 58 women who completed T1 assessment, 56 (97%) found the intervention to be useful. FCR severity decreased significantly at T1 (F = 18.5, effect size = 0.39, P < .0001) and T2 (F = 24, effect size = 0.68, P < .0001) compared with baseline. There were no changes in unmet need or depression or anxiety. Mean consultation length was 22 minutes (range, 7-47 minutes), and mean intervention length was 8 minutes (range, 2-20 minutes). The intervention was perceived as useful and feasible by oncologists. CONCLUSION: A brief oncologist-delivered intervention to address FCR is useful and feasible, and has preliminary efficacy in reducing FCR. Plans for a cluster randomized trial are underway.